2016
DOI: 10.1038/srep32154
|View full text |Cite
|
Sign up to set email alerts
|

TGEV infection up-regulates FcRn expression via activation of NF-κB signaling

Abstract: It has been well characterized that the neonatal Fc receptor (FcRn) transports maternal IgG to a fetus or newborn and protects IgG from degradation. We previously reported that FcRn is expressed in a model of normal porcine intestinal epithelial cells (IPEC-J2). Transmissible gastroenteritis is an acute enteric disease of swine that is caused by transmissible gastroenteritis virus (TGEV). How porcine FcRn (pFcRn) expression is regulated by pathogenic infection remains unknown. Our research shows that IPEC-J2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In our data, many neighbouring genes correspond to compartments of the inflammatory response, such as PML (ENSSSCT00000002141), Interferon Beta 1 (IFNB1) (ENSSSCT00000005691), Radical S-Adenosyl methionine domain containing 2 (RSAD2) (ENSSSCT00000009461), and interferon induced protein with tetratricopeptide repeats 5 (IFIT5) (ENSSSCT00000011440). Previous studies have shown that NF-κB signaling pathway, one of the most important pathways, plays an important role during TGEVinduced inflammatory response [9,16,39,40]. Therefore, changes in the expression levels of genes, which related in NF-κB signaling pathway, might influence the TGEV-induced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In our data, many neighbouring genes correspond to compartments of the inflammatory response, such as PML (ENSSSCT00000002141), Interferon Beta 1 (IFNB1) (ENSSSCT00000005691), Radical S-Adenosyl methionine domain containing 2 (RSAD2) (ENSSSCT00000009461), and interferon induced protein with tetratricopeptide repeats 5 (IFIT5) (ENSSSCT00000011440). Previous studies have shown that NF-κB signaling pathway, one of the most important pathways, plays an important role during TGEVinduced inflammatory response [9,16,39,40]. Therefore, changes in the expression levels of genes, which related in NF-κB signaling pathway, might influence the TGEV-induced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase reporter plasmids FcRn-Luc, NF-κB-Luc, pR-TK, p65-EGFP, and p65-Tag2B were prepared in our laboratory and have been described previously. Genes encoding TGEV proteins were amplified from the genomic RNA of the TGEV strain WH-1 and then cloned into the expression vector pCAGGS-HA (Guo et al, 2016b) (Table 1). pCAGGS-N was used as a template to amplify several deletion mutants of the virus N gene.…”
Section: Plasmid Construction and Sirnamentioning
confidence: 99%
“…Proteins were separated via SDS-PAGE and then electrotransferred onto a polyvinylidene difluoride membrane (Bio-Rad, United States). Western blot analysis was performed using the indicated antibodies following the procedure as described previously (Guo et al, 2016b). IPEC-J2 cells grown in a six-well plate were infected with TGEV, the supernatant of IPEC-J2 cells was harvested, and IL-1β, IL-6, IL-8, TGF-β, and TNF-α protein levels were measured with a Quantibody Porcine Cytokine Array 1 (Ray Biotech, Norcross, GA, United States) according to the manufacturer's instructions.…”
Section: Western Blot and Porcine Cytokine Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Severe gastroenteritis is a significant clinical sign of TGEV infection, and it is now well-established that NF-κB is a key regulator of inflammation because of its ability to induce the transcription of pro-inflammatory genes such as tumor necrosis factor α (TNF-α), interleukin (IL) −1β, IL-6, and IL-8 [14,15]. In the current study, we found that TGEV infection induced the inflammatory response through NF-κB signal activation, but that NF-κB inhibition did not significantly affect TGEV replication.…”
Section: Introductionmentioning
confidence: 99%